Data Guide Manual and Survey Questions - PEPSO (Poverty and Employment Precarity in Southern Ontario (PEPSO) research group, 2016)
This is the data guide for using the PEPSO Employment Precarity Index that was developed for and used data from two major surveys of workers in the Greater Toronto Area and Hamilton in Ontario, Canada. These two surveys were published in the reports It’s More than Poverty in 2013 and The Precarity Penalty in 2015. The purpose of this guide is to provide instructions for using the Employment Precarity Index so that other researchers may replicate it for their own purposes. This guide is for the use of researchers who already have the PEPSO data set.
How to consruct the Precarity Index
Keywords: Survey guide